Solving the burgers' and regularized long wave equations using the new perturbation iteration technique. Issue 5 (27th September 2017) - Bildik, Necdet; Deniz, Sinan
Abstract : In this study, an efficient framework is provided to handle nonlinear partial differential equations by implementing perturbation iteration method. This method is recovered and amended to solve the Burgers' and regularized long wave equations. Comparing our new solutions with the exact solutions reveals that this technique is extremely accurate and effective in solving nonlinear models. Convergence analysis and error estimate are also supplied using some critical theorems.